Detection of endometriosis using immunocytochemistry of P450 Aromatase expressions in eutopic endometrial cells obtained from menstrual sloughing: a diagnostic study - Madjid, Tita Husnitawati (BMC Res Notes, 2020)
OBJECTIVE: To explore the possibility of a new diagnostic approach of endometriosis based on immunocytochemistry scoring of Aromatase P450 expressions in endometrial cells collected from menstrual sloughing. This is a case control study. Immuncytochemistry scores vs. histopathological examination in one tertiary- and secondary-level hospital in Bandung; two secondary level hospital in Garut and Sumedang, West Java, Indonesia. Thirty-five patients with and without endometriosis were enrolled. All subjects had diagnostic procedures for endometriosis suspicion, with addition menstrual blood samples for cytopathological examination. The specimens were sent for immunocytochemistry assessment of P450 Aromatase expressions (ICAPEC). The previous procedure resulted in cut-off point of histo score (H-score), sensitivity, specificity, (+) and (−) ICAPEC predictive value. RESULTS: The P450 Aromatase expression in endometrial cells of women with endometriosis was significantly stronger than without one. The cut-off point of H-scores to detect endometriosis was > 4. By this criteria, H-score had 94.6% sensitivity, 90.9% specificity, 92% positive predictive value and 93% negative predictive value. Immunocytochemistry scoring of Aromatase P450 expression in endometrial cells (ICAPEC) derived from menstrual blood specimen was a good candidate as alternatives approach in diagnostic procedure of endometriosis. Application and evaluation in clinical practice would provide the economically benefit in diagnostic procedure.